Green sweet potato leaves increase Nrf2-mediated antioxidant activity and facilitate benzo[a]pyrene metabolism in the liver by increasing phase II detoxifying enzyme activities in rats. Issue 14 (1st July 2022) - Yang, Ray-Yu; Zongo, Abel Wend-Soo; Chen, Yu-Chen; Chiang, Meng-Tsan; Zogona, Daniel; Huang, Chun-Yin; Yao, Hsien-Tsung
Abstract : Green and purple SPL consumption may enhance the Nrf2-mediated hepatic antioxidant activity and modulate xenobiotic-metabolizing enzymes and transporters via different mechanisms. Abstract : Sweet potato leaves (SPL) are a valuable source of phytonutrients with nutritional and various health-promoting benefits. This study evaluated the effects of green and purple SPL supplementation on hepatic xenobiotic-metabolizing enzymes (XME) and membrane transporters, and benzo[ a ]pyrene (B[ a ]P) metabolism and B[ a ]P accumulation in rats. The experiments were conducted in standard and B[ a ]P-treated rat models. The first experiment showed that rats fed a diet containing 5% (w/w) green or purple SPL for two weeks showed increased hepatic activity of cytochrome P-450 (CYP)1A1/1A2 and glutathione S-transferase. Green SPL supplementation also increased the CYP2C, CYP2D and CYP3A and multidrug resistance-associated protein 2 levels in the liver. Notably, green and purple SPL induced nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 protein expression and reduced oxidative stress in the liver. The second experiment was to evaluate the effects of green and purple SPL supplementation on B[ a ]P metabolism and B[ a ]P accumulation in rats. Rats were fed SPL diets (the same as experiment I) for two weeks. When rats were exposed to a single dose (25 mg per kg BW) of B[ a ]P, green SPL had no effect on B[ a ]P-induced elevation of CYP1A1 activity but induced GST activity in the intestinal mucosa and the liver. Green SPL also increased hepatic UDP-glucuronosyltransferase activity and reduced B[ a ]P levels in the plasma, liver, and intestinal mucosa. A lower plasma 8-hydroxy-2′-deoxyguanosine level was found after B[ a ]P treatment only in the green SPL group. This study suggests that, in the standard rat model, green and purple SPL may increase Nrf2-mediated antioxidant activity and facilitate the xenobiotic detoxification process by increasing hepatic XME and transporters. When exposed to B[ a ]P, however, only green SPL consumption may increase hepatic B[ a ]P metabolism and lower the B[ a ]P level in the liver by increasing phase II detoxifying enzyme activities.